Simultaneous Synthesis and Consolidation of Nanostructured ZrB2-ZrO2 Composite - Kim, Seong-Eun; Yoon, Jin-Kook; Shon, In-Jin (AMER SCIENTIFIC PUBLISHERS, 2020)
A dense nanostructured 2ZrB(2)-ZrO2 composite was synthesized by the high-frequency induction heated combustion synthesis (HFIHCS) method within 2 min in one step from mechanically activated powders of 2B(2)O(3) and 3Zr. Simultaneous combustion synthesis and densification were accomplished under the combined effects of the induced current and mechanical pressure. A highly dense 2ZrB(2)-ZrO2 composite with relative density of up to 95.5% was produced under the simultaneous application of a pressure of 80 MPa and the induced current. The average grain size and mechanical properties (hardness and fracture toughness) of the composite were investigated.